INFLUENCE OF AUDITOR INDEPENDENCE AND GOOD CORPORATE GOVERNANCE TOWARD ACCOUNTING CONSERVATISM IN INDONESIA - Dovi Septiari; Wirdani Atika Sari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
Accounting conservatism is the precautionary principle to the profit recognition and one of the corporate governance to reduce the ability of the manager in manipulate and exaggerating the financial statements. Corporate governance is a internal control system which has its business objectives through securing company’s assets. This research is aiming to see the correlation among auditor independence and good corporate governance in accounting conservatism. Characteristics of good corporate governance in this are managerial ownership, profitability, company size and leverage. This research uses two measurements of conservatism non operating accrual and market to book ratio. This research as carried out at manufacture company in the Indonesia Stock Exchange in 2010-2014. Sample selection do by purposive sampling method and obtained 49 companies in criteria accordingly. This research used data analysis and multiple liniear regression program eviews 9. The result showed that the effect of auditor independence is not significant in accounting conservatism in indonesia. Good corporate governance influential only the size of the company and ownership. The measurement of non operating accrual and market to book ratio show different results. Further research is expected to use another proxy for other variables to measure accounting conservatism.